Exploring the mediating role of blood metabolites in the relationship between gut microbiota and gastric cancer risk: a Mendelian randomization study - Li, Xiaocheng; Lin, Huapeng; Peng, Jing; Gong, Jianping (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPrior studies have established correlations between gut microbiota (GM) dysbiosis, circulating metabolite alterations, and gastric cancer (GC) risk. However, the causal nature of these associations remains uncertain.MethodsWe utilized summary data from genome-wide association studies (GWAS) on GM (European, n=8,956), blood metabolites (European, n=120,241; East Asian, n=4,435), and GC (European, n=476,116; East Asian, n=167,122) to perform a bidirectional Mendelian randomization (MR) analysis, investigating the causal effects of GM and metabolites on GC risk. Additionally, we conducted mediation analysis (two-step MR) to identify potential metabolite mediators in the GM-GC relationship.ResultsWe identified twelve negative and seven positive associations between specific GM taxa and GC risk. For blood metabolites, seven traits were found to be significantly associated with reduced GC risk in the European population, with these findings subsequently validated in the East Asian cohort. Three GM taxa showed potential causal associations with five metabolic traits: the Bacteroidia class and Bacteroidales order were positively correlated with five metabolites (all P < 0.013), while Bacteroides OTU97_27 exhibited a negative correlation with one metabolite (P = 0.007). Two-step MR analysis indicated that total lipids in intermediate-density lipoprotein (IDL), IDL particle concentration, phospholipids in medium low-density lipoprotein (LDL), phospholipids in small LDL, and free cholesterol in small LDL indirectly influenced the association between Bacteroidia class/Bacteroidales order and GC, with mediation proportions of 1.71% (P = 0.048), 1.69% (P = 0.048), 2.05% (P = 0.045), 1.85% (P = 0.048), and 1.99% (P = 0.045), respectively.ConclusionThe present study provides suggestive evidence of a causal relationship between specific GM, blood metabolites, and GC risk, potentially offering new insights into GC etiology.